Implementatıon Of It Governance In An Automotıve Company In Batam Cıty Usıng Cobıt 5 Framework (A Case Study At Pt Xyz) - Vicco Leonardo; Eryc Eryc (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
The governance of Information Technology (IT) plays a crucial role in the success of automotive companies in the current digital era. This thesis aims to analyze and implement IT governance using the COBIT 5 Framework in automotive companies located in Batam City. The research involves a case study to enhance the efficiency, reliability, and security of the company's IT systems. The research methodology involves data collection through interviews with various stakeholders of the company, observation, and analysis of relevant documents. The research results indicate that the implementation of the COBIT 5 Framework can assist automotive companies in identifying and addressing existing IT governance issues. By following the steps outlined in the COBIT 5 Framework, companies can improve the management of IT resources, and risk control, and enhance the quality of IT services provided. The findings of this research provide practical guidance for automotive companies in Batam City and similar enterprises to enhance their IT governance, thereby supporting growth and competitiveness in the highly competitive automotive market.